PETUALANGAN KSATRIA MINANGKABAU MELAWAN BUDAYA ASING DALAM MEDIA KOMIK - Drs. Abd. Hafiz, M.Pd., Ryan Desriandeva, Drs. Syafwan, M.Si., (Jurusan Seni Rupa FBS UNP Padang, 2016)
Generally, the design of this comic to visualize The Minangkabau Cultural Preservation and to prevent damage of foreeign cultural influences in this comic. The embodiment of the concept, the author takes issue in Minangkabau who tainted by foreign cultures. In particular, the purpose of this comic to message to the public for better preserve the Minangkabau cultural's development and visualize the Minangkabau cultural into comic with manga style. The methods used in the manufacture of this final works consists of the preparation, elaboration, synthesis, the realization of the concept and the comletion of the final works to the exhibition.Kata Kunci : : Perancangan, Komik, Memperjuangkan kebudayaan Minangkabau dari Budaya Asing.